2023
DOI: 10.1001/jama.2023.10598
|View full text |Cite
|
Sign up to set email alerts
|

Continuous vs Intermittent Meropenem Administration in Critically Ill Patients With Sepsis

Abstract: ImportanceMeropenem is a widely prescribed β-lactam antibiotic. Meropenem exhibits maximum pharmacodynamic efficacy when given by continuous infusion to deliver constant drug levels above the minimal inhibitory concentration. Compared with intermittent administration, continuous administration of meropenem may improve clinical outcomes.ObjectiveTo determine whether continuous administration of meropenem reduces a composite of mortality and emergence of pandrug-resistant or extensively drug-resistant bacteria c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 52 publications
4
41
0
Order By: Relevance
“…Augmented kidney clearance occurs in approximately 20% of patients with critical illness, especially in younger patients, in those with burns, and during the first week of hospital admission . None of these circumstances were frequent in the MERCY trial; patients were older (mean age, 64 years) and mainly had respiratory infections (33% of patients). Meropenem therapy was usually initiated later than 1 week after hospital admission, following failure of other antibiotics (66% were already receiving treatment at randomization).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Augmented kidney clearance occurs in approximately 20% of patients with critical illness, especially in younger patients, in those with burns, and during the first week of hospital admission . None of these circumstances were frequent in the MERCY trial; patients were older (mean age, 64 years) and mainly had respiratory infections (33% of patients). Meropenem therapy was usually initiated later than 1 week after hospital admission, following failure of other antibiotics (66% were already receiving treatment at randomization).…”
mentioning
confidence: 99%
“…In the MERCY trial, continuous administration of meropenem, compared with intermittent boluses, did not significantly decrease the composite primary outcome of all-cause mortality and emergence of pandrug-resistant or extensively drug-resistant bacteria at day 28 (47% vs 49%, respectively; relative risk [RR], 0.96 [95% CI, 0.81-1.13]; P = .60) . The GFR estimated with the Cockroft-Gault equation was available for 586 of 607 patients randomized in the MERCY trial, and only 94 patients (16%) had a GFR of 130 mL/min/1.73 m 2 or greater.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor The MERCY randomized clinical trial in critically ill patients with sepsis found that the meropenem dosing strategy (continuous infusion vs intermittent bolus) did not improve the composite outcome of mortality and emergence of drug-resistant bacteria. However, we are concerned that the population for whom the administration of meropenem as a continuous infusion is expected to be most beneficial was not well represented in the trial.…”
mentioning
confidence: 99%